SEPOTONG CERITA SIMBOLIS PRODUK CAKWE: ANTARA BRAND DAN JUGA DENDAM KESUMAT - Ichwan, ichwan Prastowo; Wibiyanto, Agung; Resmi, Prasiwi Citra (Jurnal Pariwisata Indonesia, 2024)
The purpose of this article is to review a symbolic story behind the Cakwe product, exploring the connection between the brand and a deep-seated grudge. This traditional pastry, originally from China, has a long history, both symbolically and culturally, which is not widely known to the public. The research method used in this article is qualitative with descriptive analysis. The data utilized comes from references, including books and journals, which will be reduced and analyzed to form this writing. The result of this paper highlights the symbolism behind the Cakwe shape, which is long and made from two dough pieces, symbolizing the bodies of Prime Minister Qin Hui and his wife, who were blamed for the death of General Yue Fei. In terms of language connotation, both in Hokkien and Cantonese, or other Southern Chinese dialects, Cakwe can be interpreted as "ghosts fried" in hot oil. While many traditional Chinese pastries are often perceived as beautiful and charming, Cakwe is considered eerie. Therefore, it is clear that the Cakwe brand has a strong connection to the narrative story that envelops the product, reflected in its shape—two human-like bodies fried in hot oil. This hot oil is also a symbolic reference to the burning oil of hell used to punish the guilty in the afterlife. Furthermore, the motif of public vengeance has been passed down through generations, evident in the long shape and texture of Cakwe, consisting of two dough pieces resembling the bodies of Prime Minister Qin Hui and his wife.